Bagaimana Latar Belakang Sosial Ekonomi Orang Tua Menentukan Prestasi Siswa - Krisma Haryuniati (Journal on Education, 2025)
The purpose of this study was to analyse SES variables that have an influence on learning achievement. This research method uses literature review. The data used comes from books and scientific journals that are relevant to the theme of the paper. SES variables used by researchers to measure the influence of SES on learning achievement include parents‘ educational background, occupation, parents’ income, parents' involvement, and family wealth or assets. Each of these indicators supports each other on student learning achievement. This finding shows that the higher the socioeconomic status of parents, the higher the student learning achievement. So the socioeconomic status of parents can affect student learning achievement directly or indirectly. The conclusion of the findings of this study from the educational background of parents, occupation, parental income, parental involvement, and family wealth or assets, each of these indicators supports each other on student learning achievement because the socioeconomic status of parents has a strong impact on student learning achievement